Dynamics of Non-visual Responses in Humans: As Fast as Lightning? - Prayag, Abhishek S.; Jost, Sophie; Avouac, Pascale; Dumortier, Dominique; Gronfier, Claude (Frontiers in Neuroscience, 2019)
The eye drives non-visual (NV) responses to light, including circadian resetting, pupillary reflex and alerting effects. Initially thought to depend on melanopsin-expressing retinal ganglion cells (ipRGCs), classical photopigments play a modulatory role in some of these responses. As most studies have investigated only a limited number of NV functions, generally under conditions of relatively high light levels and long duration of exposure, whether NV functions share similar irradiance sensitivities and response dynamics during light exposure is unknown. We addressed this issue using light exposure paradigms spectrally and spatially tuned to target mainly cones or ipRGCs, and by measuring longitudinally (50 minutes) several NV responses in 28 men. We demonstrate that the response dynamics of NV functions are faster than previously thought. We find that the brain, the heart, and thermoregulation are activated within 1 to 5 minutes of light exposure. Further, we show that NV functions do not share the same response sensitivities. While the half-maximum response is only ~45 s for the tonic pupil diameter, it is ~12 minutes for EEG gamma activity. Most non-visual responses seem to be saturated by low light levels, as low as 90 melanopic lux. Our results also reveal that it is possible to maintain optimal visual performance while modulating non-visual responses. Our findings have real-life implications. On one hand, light therapy paradigms should be re-evaluated with lower intensities and shorter durations, with the potential of improving patients’ compliance. On the other hand, the significant impact of low intensity and short duration light exposures on non-visual physiology should make us reconsider the potential health consequences of light exposure before bedtime, in particular on sleep and circadian physiology.